Single-Session Therapy by Appointment for the Treatment of Anxiety Disorders in Youth and Adults: A Systematic Review of the Literature - Bertuzzi, Vanessa; Fratini, Giulia; Tarquinio, Claudia; Cannistrà, Flavio; Granese, Valentina; Giusti, Emanuele Maria; Castelnuovo, Gianluca; Pietrabissa, Giada (Frontiers in Psychology, 2021)
Purpose: This systematic review provides a summary of the available evidence of the efficacy of single-session therapy (SST) on anxiety disorders in both youth and adults. Methods: PubMed, Scopus, Medline, and Google Scholar databases were search for relevant articles, and the Cochrane Collaboration's tool for assessing the risk of bias in randomized trials was used for transparent reporting of the methodological quality of each selected study. Results: The search of electronic databases identified 18 reports based on rigorous inclusion criteria. SST was found superior to no treatment in reducing anxiety symptoms, and similar results were observed while comparing SST to multi-treatment sessions. Discussion: The findings support the benefits of SST in enhancing cognitive, behavioral, and psychological outcomes in both youth and adults suffering from anxiety disorders across treatment conditions and approaches, SST thus appears to be a promising way of providing access to both private and public therapeutic services efficiently and cost-effectively. Conclusions: SST is effective in treating anxiety disorders. Further research is required to quantify its cost-effectiveness and deepen the knowledge of effective treatment ingredients for both young people and the adult population suffering from diverse anxiety disorders